Research on mapping method of logical carrying network across multiple domains - Min ZHANG; Chun-ming WU; Bin WANG; Ming JIANG (Tongxin xuebao)
In order to solve the mapping problem of logical carrying network across multiple domains,a hierarchical linear program model was presented,which aims to minimize the cost of mapping.Based on this model,a mapping algorithm for logical carrying network across multiple domains was designed using primal decomposition and subgradient optimization technique.The correctness of this method was proved by theoretical analysis,and the validity of the proposed method was assessed by a collection of numerical simulation experiments through the performance of convergence and runtime,as well as mapping request acceptance ratio and revenue in a dynamical network environment.